Prognostic Factors and Effect of Adjuvant Chemoradiation Following Chemotherapy in Resected Pancreatic Cancer Patients With Lymph Node Metastasis or R1 Resection - Xing, Jiazhang; Yang, Bo; Hou, Xiaorong; Jia, Ning; Gong, Xiaolei; Li, Xiaoyuan; Zhou, Na; Cheng, Yuejuan; Bai, Chunmei (Frontiers in Oncology, 2021)
Pancreatic ductal adenocarcinoma (PDAC) is a lethal disease with a poor prognosis. In resectable PDAC, the recurrence rate is still high even when surgery and adjuvant chemotherapy (CT) are applied. Regional lymph node metastasis and positive margins are associated with higher recurrence risk and worse survival. Adjuvant radiotherapy has been explored, but its efficacy remains controversial. In recent years, some characteristics have been reported to stratify patients who may benefit from adjuvant chemoradiation (CRT), such as lymph node metastasis and margin status. Adjuvant chemotherapy followed by chemoradiation (CT-CRT) was also proposed. A total of 266 patients with resectable PDAC who have lymph node metastasis or R1 resection after surgery were enrolled. In multivariate Cox regression analyses, pancreatic body or tail tumor location (HR 0.433, p<0.0001, compared with pancreatic head) and adjuvant CT predicted a better survival, while there were no significant differences among the different CT regimens. Higher T stage indicated poor survival (stage I: reference; stage II: HR 2.178, p=0.014; stage III: HR 3.581, p=0.001). Propensity score matching was applied in 122 patients to explore the role of CRT. A cohort of 51 patients (31 and 20 patients in the CT and CT-CRT groups, respectively) was generated by matching. Further analyses revealed adjuvant CT-CRT was associated with prolonged survival compared with CT alone (HR 0.284, p=0.014) and less frequent local recurrences (56.5% vs. 21.4% in the CT and CT-CRT group, respectively). However, no significant differences in disease-free survival among these two groups were observed.